What Is Meant by “Replication” and Why Does It Encounter Resistance in Economics? - Duvendack, Maren; Palmer-Jones, Richard; Reed, W. Robert (American Economic Review, 2017)
This paper discusses recent trends in the use of replications in economics. We include the results of recent replication studies that have attempted to identify replication rates within the discipline. These studies generally find that replication rates are relatively low. We then consider obstacles to undertaking replication studies and highlight replication initiatives in psychology and political science, behind which economics appears to lag.